(untitled) (Nóema, 2020)
The aim of this paper is to describe Whitehead’s specific interpretation of what was originally Plato’s concept of the "receptacle" (hypodoché). Whitehead, in line with his own process philosophy, understands Plato’s concept of the "receptacle" as a personal unity that, in its structural character, expresses the general principle that determines the constitution of the whole of our reality. The author of this paper begins by briefly describing Plato’s concept of hypodoché. The author then goes on to present Whitehead’s specific interpretation of this concept, which allows him to elaborate the potential parallels between Whitehead’s interpretation of hypodoché and his concept of "eternal objects". Finally, the author attempts to find the answer to a fundamental philosophical question: what in reality corresponds to Whitehead’s concept of "eternal objects". He suggests that a possible answer may be found in the General Systems Theory of Ludwig von Bertalanffy.